Developing The Participative and Collaborative Scientific Writing Materials to Develop The Students’ Social and Emotional Intelligence - Supriyadi, Supriyadi (Technium Social Sciences Journal, 2021)
The research was aimed at enhanching social, emotional intelligence of students by developing participative, collaborative scientific writing teaching materials based on need analysis. It has three focuses, i.e. introduction study, product design and development, and product effectivity test. The research data consists of field notes, feedback, comments and critics on the product from experts and practitioners. The data is analyzed by using domain analysis technique. The research results in developed product of participative, collaborative scientific writing teaching materials. It has specific characteristics that were different from conventional teaching materials, which have reflection of student participation in identifying purpose and selection of teaching materials that can be used as collaborative, democratic discussion topic for the students. The effectivity test results show that the developed product was better than conventional scientific writing teaching materials. Scientific writing teaching and learning process that utilizes the developed teaching material product significantly impacts on improved social, emotional intelligence, teaching and learning process quality, and scientific writing learning achievement of students. The research results show that all teaching materials used in teaching and learning process at higher education institutions, particularly at Study Program of Indonesian Language and Literature Education, should get through series of development process testing to produce excellent, high quality teaching materials.The research was aimed at enhanching social, emotional intelligence of students by developing participative, collaborative scientific writing teaching materials based on need analysis. It has three focuses, i.e. introduction study, product design and development, and product effectivity test. The research data consists of field notes, feedback, comments and critics on the product from experts and practitioners. The data is analyzed by using domain analysis technique. The research results in developed product of participative, collaborative scientific writing teaching materials. It has specific characteristics that were different from conventional teaching materials, which have reflection of student participation in identifying purpose and selection of teaching materials that can be used as collaborative, democratic discussion topic for the students. The effectivity test results show that the developed product was better than conventional scientific writing teaching materials. Scientific writing teaching and learning process that utilizes the developed teaching material product significantly impacts on improved social, emotional intelligence, teaching and learning process quality, and scientific writing learning achievement of students. The research results show that all teaching materials used in teaching and learning process at higher education institutions, particularly at Study Program of Indonesian Language and Literature Education, should get through series of development process testing to produce excellent, high quality teaching materials.